Does Corporate Social Responsibility Spending Enhancing the Financial Performance? - Matar, Ali (International Journal of Applied Research in Management and Economics, 2022)
This paper examines the dynamic relationship between financial performance FP and corporate social responsibility spending CSRS in Jordan. The dynamic panel system GMM measurement was utilized for 164 listed companies in Amman stock Exchange. The results demonstrate that CSRS and accounting-based measurement have a beneficial association. There are no correlations between CSRS and market-based measurement, on the other hand. The findings indicated that Jordanian listed companies have a lot of room for improvement when it comes to exposing their CSR efforts across multiple dimensions, which might help the Jordanian government with its ongoing initiatives of social and economic transformation.